(untitled) (South East Asia Journal of Public Health, 2016)
Patients with diabetes are considered to be at more risk of dyslipidemia and hypertension, hence targets for cardiovascular diseases. This study describes the possible role of Glycated Hemoglobin (HbA1c) and serum lipid profile as a biomarker in the detection of cardiovascular diseases. A cross-sectional study was carried out on 54 (33 males and 21 females) type 2 diabetes (T2DM) patients at Ayub Teaching Hospital (ATH), Abbottabad and Mardan Medical Complex (MMC), Mardan, Khyber Pukhtunkhwa (KP), Pakistan. The control group comprised of 20 (13 males and 7 females) healthy human samples. The patients had significantly higher (p<0.05) Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), HbA1c, Fasting Blood Glucose (FBG), Total Cholesterol (TC), Triglyceride (TG) compared to control subjects. Only High Density Lipoprotein (HDL) was found to be significantly (p<0.05) lower in the patients compared to controls. With regards to gender, in the female patients SBP, DBP, TC and Low Density Lipoprotein (LDL) were significantly higher (p<0.05) compared to males patients. The HbA1c was found to be significantly higher (p<0.05) in males. Results also revealed that patients having HbA1c>7.0%, had higher TG than those with HbA1c?7.0%. Furthermore, 14.2% patients with HbA1c>7.0% had cerebrovascular diseases and 28% have ischemic heart diseases. The findings of the current study suggests association of HbA1c with lipid profile in T2DM patients and both might be used as a predictor of cardiovascular diseases in such patients. South East Asia Journal of Public Health Vol.5(2) 2015: 30-34